Scale up of biopolymer (PHB) fermentation from shake flask to 10L stirred tank fermenter and optimization of levels of variables at 10L - Mohd Hishafi, Husin (2009)
In this research is about the fermentation process for PHB production by Cupriavidus necator using glucose as a substrate. The different parameters of glucose concentration and agitation speed were studied. There are two stages in this research. For the first stage, the scale-up process was done from shake flask to 10L fermenter based on constant volumetric mass transfer coefficient KLa. The shake flask agitation speed of 200 rpm and temperature 30°C were used as the basis of scale up. The result gives the PHB yield for shake flask and 10L as 60.12mg/L and 60.19 mg/L respectively. From these results, it can be concluded that the first stage had achieved its objective. For the second stage, optimization of variables was done by using glucose concentration; 10g/L and 30g/L and agitation speed; 200 rpm and 260 rpm as the manipulated variables. It was observed that the PHB yield is affected by initial glucose concentration of glucose used and also by the agitation speed.